2019
DOI: 10.15171/ehem.2019.25
|View full text |Cite
|
Sign up to set email alerts
|

Removal of styrene by the synthesized ZnO nanoparticles coated on the activated carbon adsorbent in the presence of UV irradiation

Abstract: Background: Volatile organic compounds are the major environmental pollutants causing adverse effects on the human health and the environment, therefore, tremendous effort has been put toward eliminating these compounds. Methods: In this study, the effect of synthesized nanoparticles on the removal of styrene from gas phase by photocatalytic process under UV irradiation in the cylindrical photoreactor was studied. The activated carbon-zinc oxide (AC-ZnO) catalysts were prepared at different weight ratios (6%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(47 reference statements)
1
1
0
Order By: Relevance
“…Wang et al in their study on the synthesis of ZnO nanoparticles by hydrothermal synthesis method found similar results, which is consistent with the results of this study (24). In the investigation of TEM images, the small size of ZnO nanoparticles confirmed that a high specific surface area could show a good catalytic activity (15,20). The EDS spectrum of ZnO nanoparticles shows four peaks, which are identified as Zn and O.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Wang et al in their study on the synthesis of ZnO nanoparticles by hydrothermal synthesis method found similar results, which is consistent with the results of this study (24). In the investigation of TEM images, the small size of ZnO nanoparticles confirmed that a high specific surface area could show a good catalytic activity (15,20). The EDS spectrum of ZnO nanoparticles shows four peaks, which are identified as Zn and O.…”
Section: Discussionsupporting
confidence: 88%
“…In the last two decades, photocatalysts using semiconductor materials such as ZnO have attracted special attention due to their high optical sensitivity, high stability wide band gap and high efficiency in electron production. Using these nanoparticles, the energy Gap's property can adsorb a wide range of UV (19)(20)(21). Because of the extensiveness of nanoparticles and their applications, different methods are used for their production, the choice of which depends on the kind of materials and their application (22,23).…”
Section: Introductionmentioning
confidence: 99%